Semi-empirical study of acetic acid esterification and methyl ester transesterification reactions with Nafion catalyst using PM7 level of theory - Alfian, Fariz R.; Faiq, Farly Y.; Rizaldy, Rafli; Haq, Kautsar Ul (Universitas Airlangga, 2022)
Nafion, as a highly acidic catalyst, is appropriate for application in both esterification and transesterification reactions. Nevertheless, its computational efficacy hasn't been explored yet. A semi-empirical approach employing the PM7 theory was utilized to determine the configurations of reactants, transition states, intermediates, and products, along with the energetics of the reactions. The findings indicate that, with Nafion catalysts, a 6-ring complex is formed in both reactions, and the rate-determining step occurs at the initial activation energy. Additionally, a quantum leap in reaction kinetics was observed in the presence of the Nafion catalyst, leading to an accelerated reaction rate.